Efektivitas Konseling Kelompok Cognitive Behavior Teknik Metakognitif dalam Mereduksi Burnout Siswa di SMA Muhammadiyah Bantul - Farah Abida Nur Allita; Akhmad Fajar Prasetya (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
The development of modern education requires students to adapt to various complex academic pressures such as heavy workloads, achievement demands, and limited time, which can trigger academic burnout. This condition negatively affects students’ motivation, concentration, and psychological well-being. This study aims to determine the effectiveness of group counseling using the metacognitive technique in reducing academic burnout among students at SMA Muhammadiyah Bantul. The research employed a one-group pretest–posttest design involving six twelfth-grade participants selected through purposive sampling. Data were collected using a Likert-scale-based academic burnout instrument that had been tested for validity and reliability. Data analysis using SPSS showed a normal distribution (Sig. = 0.200), linear relationship (0.182), and no heteroscedasticity (1.000). Hypothesis testing produced a significance value of 0.000 < 0.05 with an effect size of Cohen’s d = 7.482, indicating a strong effect. These findings demonstrate that group counseling with the metacognitive technique is effective in reducing academic burnout, enhancing self-awareness, and helping students manage academic stress, making it a useful intervention strategy for school guidance and counseling teachers.